Public management reform and the regulation of private business: risk-driven, customer-centric, and all joined-up? - Raine, John W.; Lloyd, Huw (2013)
This article considers the impacts on the public regulation of private business of three key transformations in public management: "towards more targeting of resources" (through more risk-based regulation); "towards a stronger service ethos" (through more customercentricity); and "towards increased integration" (through more joined-up regulatory organization). Empirical evidence is presented from a program of research focusing on local authority regulation of the businesses sector in England and Wales. The article concludes by reflecting on how such transformations, which are of wide international significance, might be viewed, particularly from a public interest perspective. - Reproduced.
Keywords: Administrative reform